2010
DOI: 10.1523/jneurosci.4264-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Feedforward Compensation Mediated by the Central and Peripheral Actions of a Single Neuropeptide Discovered Using Representational Difference Analysis

Abstract: Compensatory mechanisms are often used to achieve stability by reducing variance, which can be accomplished via negative feedback during homeostatic regulation. In principle, compensation can also be implemented through feedforward mechanisms where a regulator acts to offset the anticipated output variation; however, few such neural mechanisms have been demonstrated. We provide evidence that an Aplysia neuropeptide, identified using an enhanced representational difference analysis procedure, implements feedfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 72 publications
4
76
0
4
Order By: Relevance
“…CP2 antibody (rabbit) was a gift from Dr. P. Lloyd (Phares and Lloyd, 1996). FCAPb (ALDSLGGFQVHGW, ALDSLGGFQVHGW; Protein Core Facility, University of Illinois, Urbana, IL) was used to generate the antibodies in rabbits as described previously (Furukawa et al, 2001;Jing et al, 2010). Briefly, the antigen was prepared by coupling synthetic peptide to BSA (catalog #A0281; Sigma-Aldrich) using 1-ethyl-3-(dimethylaminopropyl)carbodiimide (catalog #E7750; Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…CP2 antibody (rabbit) was a gift from Dr. P. Lloyd (Phares and Lloyd, 1996). FCAPb (ALDSLGGFQVHGW, ALDSLGGFQVHGW; Protein Core Facility, University of Illinois, Urbana, IL) was used to generate the antibodies in rabbits as described previously (Furukawa et al, 2001;Jing et al, 2010). Briefly, the antigen was prepared by coupling synthetic peptide to BSA (catalog #A0281; Sigma-Aldrich) using 1-ethyl-3-(dimethylaminopropyl)carbodiimide (catalog #E7750; Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Immunocytochemistry combined with dye injection was performed as described previously (Furukawa et al, 2001;Jing et al, 2010). CBI-11 was identified based on morphology and electrophysiological characteristics and injected with carboxyfluorescein .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Groundbreaking research, as reviewed by Li et al (2000), demonstrated that neuronal circuits can be studied by MALDI MS at the single-cell level, and their chemical content correlated to animal behavior and to specific physiological states. Combined with molecular biology and electrophysiology, single-cell MS is effective for examining neuronal architecture, and for delineating neuronal circuits that regulate physiology and control of instinctive and learned behaviors (Jarecki et al, 2010;Jing et al, 2010;Vilim et al, 2010). Investigations of signaling peptides and their involvement in neural plasticity, learning, memory, complex behavior, and various physiological functions at the level of the individual cell have been successful in invertebrate models (Jimenez et al, 1994;Christie et al, 2010;Li and Smit, 2010;Neupert and Predel, 2010;.…”
Section: Power Of One: Single-cell Analysis For Circuit and Pathway Cmentioning
confidence: 99%